Detection of novel paraja ring finger 2‐fer tyrosine kinase mRNA chimeras is associated with poor postoperative prognosis in non‐small cell lung cancer. Issue 11 (5th September 2013) - Kawakami, Masanori; Ishikawa, Rie; Amano, Yosuke; Sunohara, Mitsuhiro; Watanabe, Kousuke; Ohishi, Nobuya; Yatomi, Yutaka; Nakajima, Jun; Fukayama, Masashi; Nagase, Takahide; Takai, Daiya
Abstract : Previously, we reported that the overexpression of fer tyrosine kinase (FER), a non‐receptor tyrosine kinase, is correlated with poor postoperative prognosis and cancer‐cell survival in non‐small cell lung cancer (NSCLC). In the present study, we further analyzed FER‐overexpressed NSCLC cases and identified various patterns of chimeric mRNAs, composed of paraja ring finger 2 (PJA2) and FER. We detected no genomic rearrangements between PJA2 and FER and attributed these chimeric mRNAs to alterations at the transcriptome level: i.e., trans ‐splicing. Several chimeric patterns were detected concurrently in each patient, and the pattern sets varied among patients, although the pattern in which PJA2 exon 1 was fused to FER exon 3 (designated as Pe1‐Fe3 mRNA) was detected constantly. Therefore, in a wide screening for PJA2‐FER mRNAs in NSCLC, we focused on this chimeric pattern as a representative chimera. In analyses of 167 NSCLC samples, Pe1‐Fe3 mRNA was identified in about 10% of the patients, and the presence of chimeric mRNA was significantly correlated with a high expression level of parental FER mRNA. Furthermore, we found that the detection of Pe1‐Fe3 mRNA was correlated with poor postoperative survival periods in NSCLC, consistent with a previous finding in which FER overexpression was correlated with poor postoperative prognosis in NSCLC. This report is the first to suggest a correlation between chimeric mRNA and the expression level of parental mRNA. Furthermore, our findings may be clinically beneficial, suggesting that PJA2‐FER mRNAs might serve as a novel prognostic biomarker in NSCLC.